(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Central nervous system (CNS) tumors are a diverse group of tumors of the central nervous system and have different histopathological characteristics and demographics. The clinicopathological profile of their disease is important to evaluate to understand the disease patterns and to make an accurate diagnosis. Materials and Methods: The present prospective-cum retrospective study was done in the Department of Pathology, GMC, Jammu during the six year period from August 2018 to July 2024, involving histopathologically proven CNS tumors. Clinico-radiological and histopathological evaluation was done by age, sex, site of the tumour and the morphological sub type. Results: A total of 100 CNS tumors both primary and secondary were evaluated. The most frequent tumors were meningioma (45%), astrocytic (28%), oligodendroglioma (11%), schwannoma (10%) and oligoastrocytoma (2%). With respect to age distribution, the mean age was 47.7 years and 41-50 age group had the largest number of tumors (26%), there were more female cases compared to males (53 vs. 47%). Intracranial tumors comprised 79% of cases and spinal tumors made upto 21%. The frontal lobe was the most frequently involved lobe in intracranial tumor (40.5%), followed by multilobar (24.1%) and parietal (15.2%). The most common location of tumors in the spine was the dorsal area (61.9%). In meningiomas, the most common variant was meningothelial variant (42.2%) followed by transitional and psammomatous variants (15.6% each). Conclusion: CNS tumors showed a broad histopathological spectrum with distinct age, gender and anatomical distribution patterns. Meningioma was the predominant neoplasm and intracranial tumors were more frequent than spinal tumors. Histopathological examination remains the cornerstone for accurate diagnosis and classification of CNS neoplasms.